Evaluation of Fraud and Control Measures in the Nigerian Banking Sector - Almajir, Abdulrasheed Garba; Usaini, Muhammad (International Journal of Economics and Financial Issues, 2019)
The purpose of this paper evaluation of fraud and control measures in Nigerian Banking Sector (A case study of three selected banks) is to aim at finding practical means of eliminating, reducing the incidence of fraud in our banking industries and researcher used both primary and secondary source. Questionnaire and interview were administered on a population sample of 75 person made up of both staff and management of First Bank Nigerian Plc, Union Bank of Nigerian Plc and United Bank for African all in Gusau, Zamfara state. The findings derives from respondents indicates that poor internet system not greed is the main course of fraud in the Nigerian Banking and recommendation, and solution of fraud is a means of segregation of duties, were officer that past entry should not be responsible for checking with compulsory annual holiday for all member of the staffs and organization procedure, development of a good organization structure and career opportunity for staff so as to have dedicated loyal staff and contented with force and good training programme is important for staff at all levels. Keywords: Fraud, Control, and Nigerian Banks JEL Classifications: M4, M42 DOI: https://doi.org/10.32479/ijefi.8931